The Effect of Head NumberTogether (NHT) Learning Model on Student Mathematics Learning Outcomes - Nurfaidah Afianti (Universitas Islam Jember, 2018)
The purpose of the research is to know there is significant effect of using number head together (NHT) model on the mathematic students learning outcomes. The kind of the research is eksperimental research with quantitative approach. The subjects of the research are students of class VII C at SMP Plus Bustanul Ulum Mlokorejo. With the data collecting method that used in the research are documentation, interview and test. The data analysis method that used is t test. The value of t tes is 4,11 with dk is 30 and alpha 0,05 and t tabel is 2,042 we know that t value > t table ( 4,11 > 2,042 ). So it is mean that Ha is approver and Ho is rejected, than we can say that there is significant effect of using number head together (NHT) model on the mathematic students learning outcomes Keywoard: number head together, mathematic student learning outcomes